2012
DOI: 10.17221/451/2011-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enzymatic modification on chicken surimi

Abstract: Stangierski J., Rezler R., Baranowska H.M., Poliszko S. (2012): Effect of enzymatic modification on chicken surimi. Czech J. Food Sci., 30: 404-411.The impact of the addition and duration of protein modification with transglutaminase preparation of microbial origin (MTG) of a chicken surimi on its texture, rheological characteristics, water molecular dynamics, and water activity were assessed. Surimi samples were supplemented with 0.3 g/100 g MTG and incubated maximally for about 7 h at the temperature of 15°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For all NPS pastes regardless the period of their storage in an ice shrank up to 90 days only one spin-lattice (T 1 ) and one spin-spin (T 2 ) relaxation time could be observed. It was characteristic for biopolymers pastes [35,40]. It suggested that in spite of progressing retrogradation of starches there was a fast chemical exchange, that is, the within the time necessary for the energy transfer from spin into environment as well as into to another spin, molecules of water could migrate from one fraction of water into another.…”
Section: Resultsmentioning
confidence: 99%
“…For all NPS pastes regardless the period of their storage in an ice shrank up to 90 days only one spin-lattice (T 1 ) and one spin-spin (T 2 ) relaxation time could be observed. It was characteristic for biopolymers pastes [35,40]. It suggested that in spite of progressing retrogradation of starches there was a fast chemical exchange, that is, the within the time necessary for the energy transfer from spin into environment as well as into to another spin, molecules of water could migrate from one fraction of water into another.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements of water activity were performed using the analyzer of water diffusion and activity ADA-7 (COBRABID, Pozna ń, Poland), with a system of automatic time recording of water evacuation runs from individual samples. Detailed characteristics of the experimental method were as described by Stangierski et al [37], with a slight modification [38]. The starch powders were placed in measuring vessels with a diameter of 2 cm.…”
Section: Water Activitymentioning
confidence: 99%